Responses of the Natural Phytoplankton Assemblage to Patagonian Dust Input and Anthropogenic Changes in the Southern Ocean - Clément Demasy; Marie Boye; Ambroise Delisée; Jean‐François Maguer; Melilotus Thyssen; Léa Gest (Earth's Future, 2025)
Abstract The cumulative effects of multi‐faceted changes on the phytoplankton community of the Southern Ocean (SO) are not yet known, which is a major limitation to predicting the future direction of the biological carbon pump. Thus, our study aimed to estimate the effects of intensified Patagonian dust inputs, warming and acidification on the growth, composition and production of phytoplankton assemblages in the Polar Frontal Zone (PFZ) and the High‐Nutrient Low‐Chlorophyll (HNLC) region of the Indian sector of the SO during the austral summer 2022. Natural phytoplankton communities were incubated for 5‐day under 4 scenarios (present and future conditions, and 2 intermediate scenarios). In the PFZ, +3°C and acidification stimulated the growth of phytoplankton, mainly cyanobacteria, while intensified dust inputs alone did not have notable impact. Conversely, in HNLC waters, the addition of Fe‐dust alone increased the total chlorophyll a of diatoms (mainly F. kerguelensis), whereas the negative effect of acidification and +3°C counteracted the positive impact of dust input on the diatoms. In these waters, future conditions benefited smaller species (haptophytes and cyanobacteria). The net particulate organic carbon production (POC) was also unaltered by future conditions, suggesting that primary production may not change in the future SO. However the increase in the length and number of long‐chain diatoms under future HNLC conditions may indicate that POC export could intensify in the future.